2016
DOI: 10.1111/papt.12112
|View full text |Cite
|
Sign up to set email alerts
|

Does schema therapy change schemas and symptoms? A systematic review across mental health disorders

Abstract: PurposeSchema therapy was first applied to individuals with borderline personality disorder (BPD) over 20 years ago, and more recent work has suggested efficacy across a range of disorders. The present review aimed to systematically synthesize evidence for the efficacy and effectiveness of schema therapy in reducing early maladaptive schema (EMS) and improving symptoms as applied to a range of mental health disorders in adults including BPD, other personality disorders, eating disorders, anxiety disorders, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 76 publications
4
81
0
9
Order By: Relevance
“…Given that the schema model emphasises altering EMSs as a key mechanism for change in therapy, the relief in EMSs should be expected as an outcome of treatment. A recent systematic review (Taylor, Bee, & Haddock, 2016) found that overall there is only limited evidence that EMSs change during schema therapy, as the majority of studies have not included assessment of EMSs as a treatment outcome. Furthermore, one study found that schema therapy results in similar symptomatic relief in MDD patients to that in traditional cognitive-behavioural therapy (Carter et al, 2013), and that other forms of psychotherapy might be beneficial in altering EMSs (Halford, Bernoth-Doolan, & Eadie, 2002;Wegener, Alfter, Geiser, Liedtke, & Conrad, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the schema model emphasises altering EMSs as a key mechanism for change in therapy, the relief in EMSs should be expected as an outcome of treatment. A recent systematic review (Taylor, Bee, & Haddock, 2016) found that overall there is only limited evidence that EMSs change during schema therapy, as the majority of studies have not included assessment of EMSs as a treatment outcome. Furthermore, one study found that schema therapy results in similar symptomatic relief in MDD patients to that in traditional cognitive-behavioural therapy (Carter et al, 2013), and that other forms of psychotherapy might be beneficial in altering EMSs (Halford, Bernoth-Doolan, & Eadie, 2002;Wegener, Alfter, Geiser, Liedtke, & Conrad, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since EMS are highly theoretical constructs it is important to develop instruments for their systematic assessment such as the Young Schema Questionnaire (YSQ; Schmidt, Joiner, Young, Telch, 1995). Since the development of the YSQ as a measure of EMS, a growing number of studies have signified their relevance for a range of clinical disorders with a great emphasis on chronic mental disorders (Lobbestael & Arntz, 2012;Taylor, Bee, & Haddock, 2017). This practical relevance could potentially be advanced by balancing the pathological constructs of EMS with concrete strength-focussed concepts emphasizing the fulfilment of needs (Lockwood & Perris, 2012;Seligman & Csikszentmihalyi, 2014).…”
Section: Schema Therapy the Role Of Ems And The Need For A Concept Omentioning
confidence: 99%
“…Activated EMS strongly influence how people perceive themselves and others through mechanisms of selective attention, encoding of stimuli and selective retrieval of schema-associated information (Arntz and Lobbestael, 2018). Schema therapy has been found to reduce EMS while also improving symptoms for personality disorders (Taylor et al, 2017), and in chronic depression (Renner et al, 2018). However, sound mediation-analytical studies have not been conducted yet, and evidence for other mental health disorders than personality disorders and depression is sparse (Taylor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%